Automated Erythrocytes Counting in Microscopic Thin Blood Smear Digital Images - Naveed Abbas; Dzulkifli Mohamad; Abdual Hanan Abdullah (Journal of Telematics and Informatics, 2015)
The Erythrocytes counting is part of the complete blood count test and it is frequently suggested by the Physician to know the number of Erythrocytes in the patient’s body. At present mostly the counting process is performed manually which is laborious, error prone and time consuming. The main purpose of this study is to use the digital image processing techniques to automate the counting process of the Erythrocytes or Red Blood Cells in Microscopic thin Blood smear digital images. The automated diagnosing gain the attention of the researchers from the last two decades because it assist the experts to reduce the burden of errors, labour and time of examination. In this regard, too much research has been performed on the automation of the counting process of the Erythrocytes but still the test demands to be done in a proper, efficient, accurate and realistic way. The proposed method achieved an average True Positive Rate (TPR) of 95%, True Negative Rate (TNR) of 5%, average accuracy of 97% and average error of 3%.